PENINGKATAN KOMPETENSI SUMBER DAYA MANUSIA PELAKU UMKM UNTUK MEMPERKUAT DAYA SAING PADA UMKM (STUDI FENOMENOLOGI PADA PAGUYUBAN UMKM AMREH MULYO BALETURI TEGARON) - Fitriana, Nanda Nur; Wihara, Dhiyan Septa; Soeprajitno, Edy Djoko (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
This study aims to examine, analyze and interpret in depth and explain the experiences experienced by MSME actors in the current era of globalization in order to strengthen their competitiveness. Competitiveness is very important for business continuity. In order for business development to compete in the market, MSME business actors must be able to create a conducive internal and external environment in order to create broad business opportunities and be able to maintain a healthy market mechanism. This study uses a qualitative method with a phenomenological approach. The phenomenological approach is used because this data comes from the experience of participants or events experienced by 3 participants, namely the chairman of the MSME Association, the Finance Section and workers at MSMEs. The research findings indicate that in improving the competence of human resources, several obstacles were found, such as the limited condition of human resources and the absence of training for MSMEs that hindered the development of optimal competitiveness. This makes efforts to increase the competence of human resources in MSMEs still require a lot of training, full assistance, and personal approaches from internal and external parties to increase knowledge and skills in order to strengthen the competitiveness of business units.